CO2 corrosion control in steel pipelines. Influence of turbulent flow on the performance of corrosion inhibitors. (May 2015) - Olvera-Martínez, María Elena; Mendoza-Flores, Juan; Genesca, J.
Abstract: Corrosion associated with aqueous environments containing carbon dioxide (CO2 ) and/or hydrogen sulphide (H2 S), is a well-known phenomenon in oil and gas industries. This type of corrosion is of particular importance in transportation through steel pipelines. This transportation process could involve the movement of a complex mixture of gas and liquids. This moving mixture is in close contact with the inner surface of the steel pipelines and corrosion can occur. It has been demonstrated that this corrosion is influenced by flow. In oil and gas industries, film-forming corrosion inhibitors are the main tool used to control inner corrosion in pipelines. The movement of the environment generates mechanical shear stresses on the surface of the steel that can interfere with the formation of the film. This phenomenon is frequently not taken into account in corrosion control strategies and could cause problems. Despite the importance of this, there are few scientific studies available, which can provide control criteria. This work presents some ideas developed in order to understand the influence of flow on the corrosion process, making emphasis in the corrosion process associated with carbon dioxide (CO2 ). Highlights: Corrosion data show an increasing corrosive tendency in steel pipelines due to CO2 corrosion. Internal corrosion can be significantly controlled by adding film-forming corrosion inhibitors. Turbulent flow could influence both, concentration and efficiency of a corrosion inhibitor.